Nurses in Australian acute care settings: experiences with and outcomes of e-health. An integrative review. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The World Health Organization (WHO) defines e-health as the use of information and communication technology for health [1]. The use of e-health, including electronic medical records (EMR), is a growing trend. This integrative review of the literature examines nurses experiences of e-health in Australian acute care settings. A search of the literature identified 21 papers for inclusion in this review. Two discernable themes in the literature are apparent. Research to date largely focuses on nurses experiences of e-health, including its usefulness in their work. Findings indicate that nurses attitudes to e-health and computer usage are positive, however there are indications that nurses currently using e-health in practice are often dissatisfied with the implementation of new e-health systems in their workplace and that there are a number of barriers to its successful implementation. Secondly, a discernable gap in the literature regarding the impact of e-health, and in particular EMRs, on nursing outcomes is identified with research to date limited to findings related to nursing documentation and multi-disciplinary discharge planning. Future research that considers nurse experiences in implementing e-health and applies focused strategies across a range of health settings, both in Australia and around the world, can influence successful adoption and implementation of e-health.